Pembangunan Lengkung Kadar Pengangkutan Endapan Menggunakan Fluvial-12 - Amat Sihab, Noorazlan (Universiti Sains Malaysia, 2006)
Development which takes place in river catchment areas will result in discharge and bed erosion increment or scouring and deposition. The matter stated above will result in the unstability in the river channel. When this happens, there will be failures to the river bank or in the river protection structure and reduce the channel capacity to flow the flood to downstream. Therefore, it is necessary to predict the river channel stability that will happen due to the existing development or the one which will take place in the future in a river catchment area. This study covers several locations at Sungai Kulim in Kedah. In general, this study is conducted to develop sediment rating curve using Fluvial-12 software. The development of sediment rating curve is quite important to check the stability of the reach in response to catchment changes either due to human interference or natural processes. Sediment transport data including bed load, bed material, suspended load and channel cross section is taken at several stations along Sungai Kulim to asses the available sediment transport equations and develop the sediment rating curve.